A 7000‐year high‐resolution lake sediment record from coastal central Chile (Lago Vichuquén, 34°S): implications for past sea level and environmental variability. (20th March 2017) - Frugone‐Álvarez, Matías; Latorre, Claudio; Giralt, Santiago; Polanco‐Martínez, Josué; Bernárdez, Patricia; Oliva‐Urcia, Belén; Maldonado, Antonio; Carrevedo, María Laura; Moreno, Ana; Delgado Huertas, Antonio; Prego, Ricardo; Barreiro‐Lostres, Fernando; et al.
ABSTRACT: We present a 7‐ka environmental reconstruction based on sedimentological and geochemical data from Lago Vichuquén, a coastal eutrophic lake in central Chile (34°48′S, 72°03′ W, 4 m a.s.l.). A relatively shallow and restricted marine environment with low productivity, high detrital input and dominant anoxic conditions in the Vichuquén Basin occurred from 7.0 to 6.5 cal ka BP. Rapid onset of a Holocene marine transgression at 6.5 cal ka BP favoured deeper and more biologically productive environments that existed until 2.8 cal ka BP. Bioproductivity changes during the mid‐Holocene (6.5–4.2 cal ka BP) were related to upwelling dynamics controlled by the intensity of the South‐east Pacific Anticyclone (SPA). Periods with lower organic productivity and dominant anoxic conditions reflect an increased intensity of SPA (increased upwelling) and decreased precipitation. A shift at ∼4.0 cal ka BP reflects the onset of modern Southern Westerly Winds and El Niño‐Southern Oscillation patterns. Tectonic uplifting and geormorphological activity (dune advancement) are possible reasons behind the Vichuquén Basin closure at ∼1.2 cal ka BP, leading to a low bioproductivity lacustrine environment which has developed until the present. Copyright © 2017 John Wiley & Sons, Ltd.